If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 9)(x + -1) = 0 Reorder the terms: (9 + x)(x + -1) = 0 Reorder the terms: (9 + x)(-1 + x) = 0 Multiply (9 + x) * (-1 + x) (9(-1 + x) + x(-1 + x)) = 0 ((-1 * 9 + x * 9) + x(-1 + x)) = 0 ((-9 + 9x) + x(-1 + x)) = 0 (-9 + 9x + (-1 * x + x * x)) = 0 (-9 + 9x + (-1x + x2)) = 0 Combine like terms: 9x + -1x = 8x (-9 + 8x + x2) = 0 Solving -9 + 8x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-9 + -1x)(1 + -1x) = 0Subproblem 1
Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-9, 1}
| 2x+7=-3+5x | | 5x+15=3x+8+2x-7 | | 3y-13+2y-12=180 | | 2t-83+2t-51=180 | | 14y-6=5 | | 5x-2=-x-32 | | -3r+20=15r-8 | | 11x+11+9x-11=180 | | 2t-51+2t-83=180 | | 11x+11+2y-12=180 | | 6x-7=53-4x | | 8x+4y=52 | | 2x+7=8(4+x) | | 2q-88+q+58=180 | | 2x+7=8(4+6) | | 0.3(n+4)=5 | | 90=6x-1 | | -3+4x=3x-15 | | -8+4x=6x+0 | | -4-2x-5x=80 | | 4u-42=-2(u-3) | | 6-3(1+8k)=33 | | 3(c+11)=45 | | 2msquare-50=0 | | y+7=-3(x-6) | | 6x-(4y)=8 | | B=6y-20 | | 1059.0592=38.936*w | | xy+3y=-4 | | 31=8x | | 8a-11=3a+4 | | 1300.4624=2*120.7016+L |